A case off TTP temporally associated with cocaine use: Implications for treatment of suspected DITMA. Issue 4 (18th February 2019) - Regner, Sean R.; Lerfald, Nathan
Abstract: Thrombotic microangiopathies are rare diseases associated with significant morbidity and mortality. The treatment of thrombotic thrombocytopenic purpura (TTP) and drug‐induced thrombotic microangiopathy (DITMA) remains a diagnostic dilemma as they present similarly but respond differently to standard treatment with plasma exchange. TTP is a deficiency of a disintegrin and metalloprotease with thrombospondin type 1 motif 13 resulting in von Willebrand factor aggregates. DITMA is due to vascular and platelet toxicity. Our case contradicts a notion in current literature that suggests supportive therapy when there is high suspicion for DITMA. We present what appears to be the second published case of cocaine temporally associated with TTP. Our case responded to therapy. We propose this case should influence weighing the risks and benefits of treatment of suspected DITMA and reinforces current official guidelines that suggest treating cases of suspected DITMA as TTP until the diagnosis is confirmed.